A Comparative Study on Welfare Losses of Specific Duties and Ad Valorem Duties in Monopolistic Markets - Tan, Jieyou (Transactions on Economics, Business and Management Research, 2026)
Based on the establishment of a monopoly market model, this paper conducts a comparative analysis of the welfare effects of specific tax and AD valorem tax policies. The findings show that in a monopoly market, specific taxes and AD valorem taxes have different effects on market equilibrium, consumer surplus, producer surplus, and total social welfare. By studying monopolistic markets described by linear demand functions and cost functions, we explore the pricing, output and welfare loss of monopolistic enterprises under two tax systems. The results show that the specific tax, which is a fixed unit tax rate, directly increases marginal costs, thus resulting in a small increase in monopoly prices but a significant decrease in output. AD valorem taxes, which are levied proportionally, indirectly affect pricing, and the extent of their welfare loss depends on the rate of tax and the elasticity of demand. In general, AD valorem taxes cause less unnecessary loss than specific taxes because AD valorem taxes have a certain self-regulating function, which to some extent can mitigate the adverse effects of monopoly pricing on social welfare. But when the elasticity of market demand is low or the degree of monopoly is high, the gap in welfare loss between the two will be smaller. In addition, this paper also analyzes issues such as tax revenue, administrative costs, and the possibility of policy implementation, and argues that AD valorem tax has certain advantages in terms of the stability of tax revenue and the effectiveness of anti-monopoly, but there are also problems in terms of collection costs and regulatory difficulty. Therefore, the findings of this study provide some reference value for the government in formulating tax policies in monopolistic industries. It is recommended to choose appropriate tax methods based on the characteristics of different industries, market conditions and policy goals to achieve the greatest social benefits.
Keywords: Specific taxation; AD valorem tax; Monopoly market; Loss of benefits; Unnecessary loss.